Capillary electrophoresis of neurotransmitters with amperometric detection at melanin-type polymer-modified carbon electrodes - Chicharro, M. (2004)
This paper reports on the advantages of combining the separation capability of capillary electrophoresis using a novel home-made electrochemical cell adapted to commercially available capillary electrophoresis equipment with the permselective properties of melanin-type polymer-modified carbon electrodes as amperometric detectors. The excellent permselective properties of the melanic polymer have allowed a large improvement on the quantification of dopamine, epinephrine and norepinephrine. A linear response was obtained in the range 8-200 pg of dopamine with sensitivities between 3- and 5-times higher than those at the bare carbon electrodes and detection limits at submicromolar level (41 fmol in the volume injected). The effect of the carbon electrodes size, and capillary electrophoresis parameters on the analytical performance is also discussed. © 2004 Elsevier B.V. All rights reserved.